Mouse cells transformed by bovine papillomavirus contain only extrachromosomal viral DNA sequences. - Law, M F (1981)
The viral DNA sequences in mouse C127 cells transformed by bovine papillomavirus type 1 (BPV-1) virions, by full-length linear BPV-1 DNA, or by a defined transforming subgenomic DNA segment of BPV-1 were examined by reassociation kinetics and blot hybridization. In all cases, the transformed cells contained multiple copies of BPV-1 DNA, present exclusively as supercoiled or nicked circular extrachromosomal molecules or as a slowly migrating complex of circular viral DNA molecules. In the transformed cell lines established from cells transfected with full-length linear BPV-1 DNA, there was recircularization of the input DNA which in some cases resulted in the loss of the restriction site used in the linearization of the DNA. In the transformed cell lines established with the defined subgenomic segment there was circularization of the DNA accompanied by the acquisition of new sequences or duplication and rearrangement of the BPV-1 sequences. In contrast to other well-studied virus transformation systems, no integration of the BPV-1 genome into the host chromosome could be detected under conditions sensitive enough to detect 0.1-0.2 viral genome equivalent. It was concluded that maintenance of transformation may be mediated by nonintegrated viral DNA.